Awareness and use of natural growth promoters among poultry farmers in Oyo State, Nigeria (2013)
The study investigated the awareness and use of natural growth promoters (NGPs) among poultry farmers in Oyo state. Purposive sampling was used to select 11 local government areas based on the concentration of the poultry farms and 13 respondents were randomly selected from each local government. Structured questionnaire was used to elicit information from respondents. The study revealed that69.6% of poultry farmers were males and 82.7% were within the age range of 21.50 years. Most (67.4%) of the farmers were married, 72.3% were Christian,92.8% were educated and 46.8% practice farming as major occupation. Majority (60.4%) had flock size of less than 1,000 birds and they were aware of NGPs, with feed enzymes having highest percentage (89.3%) of awareness. Feed enzymes and probiotics have the highest utilization with 87.1% and 55.0% respectively. Major constraints to utilization of NGPs are lack of extension agents, lack of knowledge of natural growth promoters, lack of technical know.how and cost of NGPs. Significant relationship was found between farmers’ educational qualification (χ2= 38.762, p= 0.010, flock size; χ2=42.078, p= 0.043 and the awareness of NGPs. Significant relationship also existed between farmers’ monthly income (χ2= 22.744, p= 0.004) flock size (χ2= 48.184, p= 0.010) and utilisation of NGPs. There is high level of awareness but utilization is low. NGPs should be subsidized and distributed through poultry farmers group.